Mîtsâqan Ghalîzan: Kajian Tafsir Ayat Al-Qur'an dan Hadis tentang Pernikahan - Asra Nur Hasanah (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2024)
Marriage in Islam is a mîtsâqan ghalîzan (a firm bond). However, in reality, marriage is often faced with various problems. This study aims to examine or explore the concept of mîtsâqan ghalîzan in marriage based on the interpretation of verses of the Qur'an and hadith, and analyze its implications for contemporary problems faced. The method used is a literature study. The results of this study explain that the importance of the concept of marriage, mîtsâqan ghalîzan in marriage as interpreted by the mufassirs. Furthermore, there is something interesting, namely, mîtsâqan ghalîzan which is associated with the existence of contemporary problems in marriage, but also provides guidance in responding to it.